The Role of Influencer Dr. Tirta in Marketing Running Shoes on Social Media and Its Impact on Generation Z’s Purchase Intention in Indonesia - Fauzan, Akbar Rizky; Setyaning, Alldila Nadhira Ayu (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study examines the role of influencers in digital marketing, focusing on Generation Z, who are highly responsive to social media content and trust-based interactions. Dr. Tirta, a credible doctor and sports figure, serves as a case study to assess his effectiveness in shaping purchase intentions for running shoes in Indonesia. The research investigates the influence of social media content, engagement and interaction, brand awareness and perception, and influencer marketing impact on Generation Z’s purchase intentions, while identifying which factors most strongly drive decisions. Using a quantitative survey design with online questionnaires and SEM-PLS analysis, the results reveal that engagement and interaction exert the most potent effect on purchase intention, followed by brand awareness and perception, and influencer marketing, with social media content also contributing positively but to a lesser extent. These findings highlight the importance of expertise-based influencers, authentic interactions, credibility, and consistent messaging in fostering consumer trust. Overall, Dr. Tirta’s role significantly influences Generation Z’s purchasing decisions, and future research should explore moderating variables, such as consumer trust and audience personality traits, to deepen the understanding of influencer marketing dynamics.